2018
DOI: 10.3390/molecules23112938
|View full text |Cite
|
Sign up to set email alerts
|

miR-103/miR-195/miR-15b Regulate SALL4 and Inhibit Proliferation and Migration in Glioma

Abstract: Glioma is the common highly malignant primary brain tumor. However, the molecular pathways that result in the pathogenesis of glioma remain elusive. In this study, we found that microRNA-103 (miR-103), microRNA-195 (miR-195), or microRNA-15b (miR-15b), which all have the same 5′ “seed” miRNA portion and share common binding sites in the SALL4 3′-untranslated region (UTR), were downregulated in glioma tissues and cell lines. These miRNAs suppressed glioma cell proliferation, migration, and invasion, induced cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…For example, Zheng et al showed the increased level of miR‐103 in colorectal cancer cells, and miR‐103 inhibition obviously suppressed the cell viability, migration, and invasion in vitro . Conversely, in glioma and non–small cell lung cancer, miR‐183 was downregulated and functions as the tumor suppressor. Our findings suggested that overexpression of miR‐103 may be useful to increase NPC cell viability, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zheng et al showed the increased level of miR‐103 in colorectal cancer cells, and miR‐103 inhibition obviously suppressed the cell viability, migration, and invasion in vitro . Conversely, in glioma and non–small cell lung cancer, miR‐183 was downregulated and functions as the tumor suppressor. Our findings suggested that overexpression of miR‐103 may be useful to increase NPC cell viability, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-195-5p may inhibit cell proliferation and induce apoptosis in glioma cells through the regulation of cell apoptosis-related proteins including Caspase-3, -8, -9 and Bcl-2 (34). Direct targets of miR-195 in glioma cells were identified as Sal-like protein 4 (35), cyclin E1 (36) to affect cell cycle (37) in the previous studies. The present study also demonstrated that miR-195-5p expression is reduced in glioma tissues and cells, and inhibition of miR-195-5p promoted cell proliferation, migration and invasion of glioma cells, and inhibited apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…For example, decreased miR-195 expression in hepatocellular carcinoma tissues significantly promotes proliferation, invasion and tumorigenesis (26). Moreover, miR-195 represses cell proliferation, migration and invasion, and accelerates apoptosis in glioma by decreasing spalt like transcription factor 4 protein expression (27). downregulation of miR-195 in colon carcinoma tissues is also associated with increased cell proliferation, migration and invasion (28).…”
Section: Discussionmentioning
confidence: 99%